Comparative Studies on the Antiplatelet Effects of a Humanized Anti-Platelet Glycoprotein IIb/IIIa Antibody (YM337) and ReoPro under Flow Conditions - Kuwahara, Mitsuhiro; Sugimoto, Mitsuhiko; Tsuji, Shizuko; Miyata, Shigeki; Nishio, Kenji; Kaku, Seiji; Suzuki, Ken-ichi; Kawasaki, Tomihisa; Yoshioka, Akira (Thrombosis and Haemostasis, 1998)
Recent clinical studies have shown that the interruption of platelet function appears to be effective for treatment of coronary occlusive diseases. For this purpose, a Fab fragment of humanized anti-platelet glycoprotein (GP) IIb/IIIa monoclonal antibody (YM 337) that exhibited an in vivo antithrombotic effect without prolongation of bleeding time in monkeys was previously characterized. In this study, the effect of YM 337 under physiological flow conditions with high or low shear rate was evaluated. The antiplatelet effects of YM 337 under varying wall shear rates were examined with the whole blood flow system. This technique allows real time visualization of the formation of fluorescence-labeled platelet thrombi on a collagen surface in a parallel plate flow chamber mounted on an epifluorescence microscope. The process of thrombus growth was also recorded in video tape and subjected to computer-assisted image analysis. We found that YM 337 displayed a high shear-preferential antiplatelet effect, while ReoPro, a control anti-GP IIb/IIIa antibody, did not show such shear dependency. The present findings therefore suggest that YM 337 might be a useful antiplatelet agent which can block pathological thrombotic events occurring under high shear, such as in coronary occlusive diseases.